Lithium secondary battery

The lithium secondary battery design with a nickel-cobalt compound, silicon-carbon mixture, and fluoroethylene carbonate addresses electrode efficiency imbalances, enhancing energy density and life characteristics by stabilizing the negative electrode.

JP2025502385AInactive Publication Date: 2025-01-24LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024542378
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-10-13
Filing Date
2023-10-11
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing lithium secondary batteries face challenges in achieving high energy density and maintaining long-term life characteristics due to imbalances in the efficiency of positive and negative electrodes, leading to negative electrode deterioration.

Method used

A lithium secondary battery design incorporating a lithium composite transition metal compound containing nickel and cobalt, a mixture of silicon and carbon active materials, and fluoroethylene carbonate, with specific efficiency constants and mixing ratios to balance electrode efficiency and improve battery performance.

Benefits of technology

The balanced electrode efficiency and use of fluoroethylene carbonate enhance battery energy density, charging performance, and extend battery life by mitigating negative electrode deterioration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502385000001
    Figure 2025502385000001
  • Figure 2025502385000002
    Figure 2025502385000002
  • Figure 2025502385000003
    Figure 2025502385000003
Patent Text Reader

Abstract

The present invention relates to a lithium secondary battery including a positive electrode, a separator, a negative electrode, and an electrolyte, in which the positive electrode includes a lithium transition metal composite compound including nickel (Ni) and cobalt (Co), the negative electrode includes a mixed negative electrode active material of a silicon-based active material and a carbon-based active material, and the electrolyte includes fluoroethylene carbonate, and the efficiency constants of the mixed negative electrode active material and the lithium transition metal composite compound and the weight part of the fluoroethylene carbonate satisfy a specific formula.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0131734, filed with the Korean Intellectual Property Office on October 13, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a lithium secondary battery. [Background technology]

[0003] Secondary batteries are widely used not only in portable devices but also in electric vehicles (EVs) and hybrid electric vehicles (HEVs) that are driven by electrical sources.

[0004] Such secondary batteries have the primary advantage of dramatically reducing the use of fossil fuels, as well as the advantage of not producing any by-products associated with energy use, and are therefore attracting attention as a new energy source that is environmentally friendly and can improve energy efficiency.

[0005] In general, a secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, an electrolyte, etc. In addition, the electrodes such as the positive electrode and the negative electrode may have an electrode active material layer provided on a current collector.

[0006] As the use of secondary batteries increases, various battery performances are required. In order to improve battery performance, appropriate attempts have been made to determine the composition of the electrode active material layer, and although some battery performances may be improved by selecting or combining materials, other performances may be deteriorated. Therefore, it is necessary to study the selection or combination of materials appropriate for the performance of the secondary battery to be improved. Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a lithium secondary battery having high energy density and excellent life characteristics. [Means for solving the problem]

[0008] One embodiment of the present invention comprises: A lithium secondary battery including a positive electrode, a separator, a negative electrode, and an electrolyte, The positive electrode comprises a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co); The negative electrode includes a mixed negative electrode active material of a silicon-based active material and a carbon-based active material, the electrolyte comprises fluoroethylene carbonate; The mixed negative electrode active material and the lithium composite transition metal compound have efficiency constants a and b, respectively, and the part by weight of the fluoroethylene carbonate is c based on 100 parts by weight of the electrolyte, where a, b, and c satisfy the following formula 1: [Formula 1] [(b / a)×100-c]≦95 Effect of the Invention

[0009] According to the embodiment described in the present specification, a high energy density can be achieved by selecting materials with excellent charge and discharge efficiency as the active materials of the positive and negative electrodes, and the efficiency constant according to the type and mixing ratio of the active materials contained in the positive and negative electrodes and the content of a specific electrolyte additive are adjusted to satisfy a specific formula, thereby achieving a balance of the efficiency of the positive and negative electrodes, thereby improving the life and fast charging performance of the battery. Specifically, fluoroethylene carbonate helps to form a coating that protects the silicon-based compound, and the appropriate ratio of fluoroethylene carbonate works effectively when the negative electrode is severely deteriorated due to the efficiency balance of the positive and negative electrodes. The more the remaining amount of fluoroethylene carbonate is, the more gas generation and cell deterioration due to side reactions occur, so an appropriate amount according to the efficiency balance of the positive and negative electrodes is necessary. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in more detail below to help understanding of the present invention. The present invention may be realized in various different forms and is not limited to the embodiments described herein. In this regard, the terms and words used in the present specification and claims are not interpreted to be limited to their ordinary or dictionary meanings, but are interpreted to have meanings and concepts that are consistent with the technical ideas of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0011] It will be understood that, as used herein, terms such as "comprising," "providing," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.

[0012] Furthermore, when a part such as a layer is said to exist "on" or "above" another part, this includes not only the case where it exists "directly above" the other part, but also the case where there is another part between them. Conversely, when a part is said to exist "directly above" another part, it means that there is no other part between them. Furthermore, being "on" or "above" a reference part means being located above or below the reference part, and does not necessarily mean being located "on" or "above" the reference part in the opposite direction of gravity.

[0013] In this specification, the term "primary particles" refers to particles that have no apparent grain boundaries when observed at a magnification of 5,000 to 20,000 using a scanning electron microscope.

[0014] In this specification, the term "secondary particles" refers to particles formed by aggregation of the primary particles.

[0015] In this specification, the term "single particle" is used to distinguish it from the commonly used conventional secondary particle-like positive electrode active material particles formed by agglomeration of tens to hundreds of primary particles, and is a concept that includes a single particle consisting of one primary particle and an agglomerate particle of 10 or less primary particles.

[0016] In this specification, the term "particle" may mean any one or all of single particles, secondary particles, and primary particles.

[0017] A lithium secondary battery according to an embodiment of the present specification includes a positive electrode, a separator, a negative electrode, and an electrolyte, the positive electrode includes a lithium composite transition metal compound including nickel (Ni) and cobalt (Co), the negative electrode includes a mixed negative electrode active material of a silicon-based active material and a carbon-based active material, and the electrolyte includes fluoroethylene carbonate. In the above embodiment, when the efficiency constants of the mixed negative electrode active material and the lithium composite transition metal compound are a and b, respectively, and the weight part of the fluoroethylene carbonate is c based on 100 weight parts of the electrolyte, a, b, and c satisfy the following formula 1.

[0018] [Formula 1] [(b / a)×100-c]≦95

[0019] The value of Equation 1 above can be calculated to one decimal place.

[0020] The charge capacity and discharge capacity of the active materials of the negative electrode and the positive electrode can be measured as follows.

[0021] First, the active material, Super-C conductive material, carboxymethyl cellulose (CMC) thickener, and styrene butadiene rubber (SBR) binder polymer were mixed in a weight ratio of 95:1:1:3 into water to prepare a slurry, which was then coated onto a copper foil to form a 1.4875 cm 2The electrode is then punched out to have an area of ​​10 mm, rolled, and dried to produce an electrode. An electrode assembly is produced by using lithium metal as a counter electrode together with the electrode and interposing a polypropylene separator between them. A non-aqueous electrolyte is produced by adding 1M LiPF6 to an organic solvent made by mixing ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7 and adding vinylene carbonate to make a concentration of 1 wt %, and then injecting the electrolyte into the electrode assembly to produce a coin half cell (CHC).

[0022] The coin-type half cell (CHC) fabricated above is charged by applying a constant current up to 0.005V at a rate of 0.2C using a CC-CV (constant current constant voltage) method, and then controlling the current at a constant voltage of 0.005V. During discharge, the charge is cut off at 1.5V using a CC (constant current) method at a rate of 0.2C, and the discharge efficiency can be measured.

[0023] The percentage ratio of the discharge capacity to the charge capacity measured using the mixed negative electrode active material as the active material, i.e., [discharge capacity (負極) / charging capacity (負極) × 100] is defined as an efficiency constant a, and the percentage ratio of the discharge capacity to the charge capacity measured using a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) as the active material, that is, [discharge capacity (正極) / charging capacity (正極) × 100] can be taken as the efficiency constant b.

[0024] The efficiency constants of the negative and positive electrode active materials may vary depending on the type and / or mixing ratio of the active materials.

[0025] The present inventors have recognized that in order to realize a high energy density of a battery, it is necessary to design a highly efficient positive electrode material and a negative electrode material with good charge / discharge efficiency, but when a silicon-based active material with a large capacity per weight is used as the negative electrode material, the low efficiency causes the deterioration of the negative electrode, which leads to a problem of deterioration of the long-term life characteristics. Therefore, the present inventors have used a silicon-based active material and a single-particle lithium nickel cobalt-based compound as the negative electrode active material and the positive electrode active material, respectively, and fluoroethylene carbonate as the electrolyte additive, and have revealed that when certain efficiency parameters are satisfied, the efficiency balance of the positive electrode and the negative electrode can be adjusted to affect the long life, thereby completing the present invention. Specifically, when the above-mentioned components contained in the positive electrode, negative electrode, and electrolyte satisfy the above formula 1, a battery with a high energy density can be realized, and the efficiency balance of the positive electrode and the negative electrode can be improved, and the life characteristics can be significantly improved.

[0026] According to one embodiment, the lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) may contain nickel in an amount of 80 mol % or more, for example, 80 mol % or more and less than 100 mol %, of the metals other than lithium. When the nickel content is high in this way, the efficiency of the positive electrode can be increased, and a high energy density of the battery can be achieved.

[0027] According to one embodiment, the lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) is a single particle.

[0028] According to one embodiment, the lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) may further contain at least one of manganese and aluminum. The lithium composite transition metal compound may contain nickel in an amount of 80 mol % or more, for example, 80 mol % or more and less than 100 mol %, of metals other than lithium. Specifically, the lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) may be represented by the following chemical formula 1.

[0029] [Chemical formula 1] Li a Ni (1-x-y) Co x M1 y M2 w O2 In Chemical Formula 1, 1.0 ≦ a ≦ 1.5, 0 ≦ x ≦ 0.2, 0 ≦ y ≦ 0.2, 0 ≦ w ≦ 0.1, 0 ≦ x + y ≦ 0.2, and M1 is at least one metal selected from Mn and Al, M2 is one or more metal elements selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb, and Mo.

[0030] According to one embodiment, the positive electrode may contain 90 to 100 parts by weight of a lithium composite transition metal compound containing the nickel (Ni) and cobalt (Co) based on 100 parts by weight of the positive electrode active material.

[0031] In one embodiment of the present specification, the silicon-based active material contains at least one of SiO x (0 ≦ x < 2), SiM y (M is a metal, 1 ≦ y ≦ 4), and Si / C. The silicon-based active material may contain only one kind or two or more kinds together. When both of the two negative electrode active material layers contain the silicon-based active material, the same kind of silicon-based active material may be used for the two active material layers, or different kinds or different combinations of silicon-based active materials may be used. The silicon-based active material may be contained in an amount of 1 part by weight or more and less than 20 parts by weight, for example, 1 to 10 parts by weight, based on 100 parts by weight of the total of the above-described mixed negative electrode active material.

[0032] The active material containing SiO x (0 ≦ x < 2) as the silicon-based active material may be silicon-based composite particles containing SiO x (0 < x < 2) and pores.

[0033] The SiO x (0 < x < 2) corresponds to a matrix in the silicon-based composite particles. The SiOx (0 < x < 2) may be in a form containing Si and SiO2, and the Si may form a phase. That is, the x corresponds to the number ratio of O to Si contained in the SiO x (0 < x < 2). When the silicon-based composite particles contain the SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.

[0034] The silicon-based composite particles may further contain at least one of a magnesium (Mg) compound and a lithium (Li) compound. The magnesium (Mg) compound and the lithium (Li) compound may correspond to a matrix within the silicon-based composite particles.

[0035] The magnesium (Mg) compound and / or the lithium (Li) compound may be present inside and / or on the surface of the SiO x (0 < x < 2). The initial efficiency of the battery can be improved by the Mg compound and / or the Li compound.

[0036] The magnesium (Mg) compound may contain at least one selected from the group consisting of magnesium (Mg) silicate, magnesium (Mg) silicide, and magnesium (Mg) oxide. The magnesium (Mg) silicate may contain at least one of Mg2SiO4 and MgSiO3. The magnesium (Mg) silicide may contain Mg2Si. The Mg oxide may contain MgO.

[0037] In one embodiment of the present specification, the magnesium (Mg) element may be contained in an amount of 0.1% by weight to 20% by weight, or 0.1% by weight to 10% by weight, based on 100% by weight of the total silicon-based active material. Specifically, the magnesium (Mg) element may be contained in an amount of 0.5% by weight to 8% by weight, or 0.8% by weight to 4% by weight. When the above range is satisfied, the magnesium (Mg) compound can be contained in an appropriate content in the silicon-based active material, so that the volume change of the silicon-based active material during charging and discharging of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0038] The lithium (Li) compound may include at least any one selected from the group consisting of lithium (Li) silicate, lithium (Li) silicide, and lithium (Li) oxide. The lithium (Li) silicate may include at least any one of Li2SiO3, Li4SiO4, and Li2Si2O5. The lithium (Li) silicide may include Li7Si2. The lithium (Li) oxide may include Li2O.

[0039] In one embodiment of the present invention, the lithium (Li) compound may include a form of lithium silicate. The lithium silicate is represented by Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and can be classified into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate may exist in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5 in the silicon-based composite particles, and the amorphous lithium silicate may be in the form of Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and is not limited to the above form.

[0040] In one embodiment of the present specification, the lithium (Li) element may be included in an amount of 0.1 wt% to 20 wt%, or 0.1 wt% to 10 wt%, based on the total weight of the silicon-based active material being 100%. Specifically, the lithium (Li) element may be included in an amount of 0.5 wt% to 8 wt%, or more specifically, 0.5 wt% to 4 wt%. When the above range is satisfied, the lithium (Li) compound can be included in the silicon-based active material in an appropriate content, so that the volume change of the negative electrode active material during charging and discharging of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.

[0041] The magnesium (Mg) or lithium (Li) content can be confirmed by ICP analysis. For the ICP analysis, a certain amount (about 0.01 g) of the negative active material is accurately taken and then transferred to a platinum crucible, and nitric acid, hydrofluoric acid, and sulfuric acid are added to completely decompose the negative active material on a hot plate. Then, an inductively coupled plasma emission spectrometry (ICPAES, Perkin-Elmer 7300) is used to measure the intensity of a standard solution prepared using a standard solution (5 mg / kg) at a wavelength specific to magnesium (Mg) or lithium (Li) element, to create a reference calibration curve. Then, the pretreated sample solution and a blank sample are introduced into the instrument, and the respective intensities are measured to calculate the actual intensities. The concentrations of each component are calculated based on the created calibration curve, and the total is converted to a theoretical value, so that the magnesium (Mg) or lithium (Li) content of the manufactured silicon-based active material can be analyzed.

[0042] In one embodiment of the present specification, a carbon layer may be provided on the surface and / or inside the pores of the silicon-based composite particles. The carbon layer imparts electrical conductivity to the silicon-based composite particles, and can improve the initial efficiency, life characteristics, and capacity characteristics of a secondary battery including a negative electrode active material containing the silicon-based composite particles. The total weight of the carbon layer may be 5% by weight to 40% by weight based on 100% by weight of the total silicon-based composite particles.

[0043] In one embodiment of the present specification, the carbon layer may include at least one of amorphous carbon and crystalline carbon.

[0044] The average particle size (D50) of the silicon-based active material may be 2 μm to 15 μm, specifically 3 μm to 12 μm, and more specifically 4 μm to 10 μm. When the above range is satisfied, the side reaction between the silicon-based composite particles and the electrolyte is controlled, and the discharge capacity and initial efficiency of the battery can be effectively achieved.

[0045] In this specification, the average particle size (D50) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve of the particles. The average particle size (D50) can be measured, for example, by using a laser diffraction method. The laser diffraction method generally allows measurement of particle sizes from the submicron range to several mm, and can obtain results with high reproducibility and high resolution.

[0046] In the present specification, the silicon carbon composite is a composite of Si and C and may be represented as a Si / C-based active material, and is distinguished from silicon carbide represented as SiC. The silicon carbon composite may be a composite of silicon and graphite, etc., and may form a structure in which a core of a composite of silicon and graphite, etc. is surrounded by graphene or amorphous carbon, etc. The silicon in the silicon carbon composite may be nanosilicon.

[0047] In one embodiment of the present specification, the carbon-based active material may be graphite, and the graphite may be natural graphite, artificial graphite, or a mixture thereof. The carbon-based active material may be included in an amount of 60 parts by weight to 99 parts by weight based on 100 parts by weight of the mixed negative electrode active material.

[0048] According to one embodiment, the negative electrode may include a current collector; and a negative electrode active material layer provided on the current collector.

[0049] The negative electrode active material may be contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less, relative to 100 parts by weight of the negative electrode active material layer.

[0050] According to one embodiment of the present specification, the negative electrode active material layer may further include a negative electrode binder in addition to the mixed negative electrode active material including a silicon-based active material and a carbon-based active material.

[0051] The negative electrode binder may improve adhesion between negative electrode active material particles and between the negative electrode active material particles and a negative electrode current collector. The negative electrode binder may be any material known in the art. Non-limiting examples of the negative electrode binder include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, and may also include various copolymers thereof.

[0052] The negative electrode binder may be included in an amount of 0.1 parts by weight to 20 parts by weight, based on 100 parts by weight of the negative electrode active material layer, for example, preferably 0.3 parts by weight to 20 parts by weight, more preferably 0.5 parts by weight to 10 parts by weight.

[0053] The negative electrode active material layer may not contain a conductive material, but may further contain a conductive material as necessary. The conductive material contained in the negative electrode active material layer is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and may be, for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fibers such as carbon fibers or metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon, aluminum, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive materials such as polyphenylene derivatives. The content of the conductive material in the negative electrode active material layer may be 0.01 to 20 parts by weight, preferably 0.03 to 18 parts by weight, based on 100 parts by weight of the negative electrode active material layer.

[0054] In one embodiment of the present specification, the negative electrode active material layer may have a thickness of 5 μm or more and 500 μm or less.

[0055] In one embodiment of the present specification, the negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has electrical conductivity. For example, the current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, or the like. Specifically, a transition metal that easily adsorbs carbon, such as copper or nickel, may be used as the current collector. The thickness of the current collector may be 1 μm to 500 μm, but is not limited thereto.

[0056] In one embodiment of the present specification, the positive electrode includes a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the lithium composite transition metal compound including nickel (Ni) and cobalt (Co). The positive electrode active material layer may have a thickness of 20 μm or more and 500 μm or less.

[0057] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has electrical conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 1 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, the positive electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0058] In one embodiment, the positive electrode active material may be contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less, relative to 100 parts by weight of the positive electrode active material layer.

[0059] According to a further embodiment of the present specification, the positive electrode active material layer may further include a positive electrode binder and a conductive material.

[0060] The positive electrode binder can improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material particles and the positive electrode current collector. Any positive electrode binder known in the art can be used, and non-limiting examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.

[0061] The positive electrode binder may be included in an amount of 0.1 parts by weight to 50 parts by weight, for example, preferably 0.3 parts by weight to 35 parts by weight, more preferably 0.5 parts by weight to 20 parts by weight, based on 100 parts by weight of the positive electrode active material layer.

[0062] The conductive material contained in the positive electrode active material layer is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.

[0063] Specifically, the conductive material may include one or more of single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs). The conductive material may be included in an amount of 0.1 to 2 parts by weight based on 100 parts by weight of the composition for the positive electrode active material layer, for example, preferably 0.3 to 1.5 parts by weight, more preferably 0.5 to 1.2 parts by weight.

[0064] The positive electrode and the negative electrode may be manufactured by a conventional method for manufacturing a positive electrode and a negative electrode, except for using the positive electrode and negative electrode active materials described above. Specifically, the active material layer forming composition containing the active material and, optionally, a binder and a conductive material may be applied to a current collector, followed by drying and rolling. In this case, the types and contents of the positive electrode and negative electrode active materials, binder, and conductive material are as described above. The solvent may be any solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the active material, conductive material, and binder in consideration of the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that can provide excellent thickness uniformity when applied to manufacture the positive electrode and the negative electrode. As another method, the positive electrode and the negative electrode can also be produced by casting the active material layer forming composition on a separate support, peeling it off from the support, and laminating the resulting film on a current collector.

[0065] The separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a secondary battery can be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a normal porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or multilayer structure.

[0066] Examples of the electrolyte include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries.

[0067] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0068] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0069] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, can be preferably used as high-viscosity organic solvents, because they have a high dielectric constant and dissociate lithium salts well. When such cyclic carbonates are mixed in an appropriate ratio with linear carbonates having low viscosity and low dielectric constant, such as dimethyl carbonate and diethyl carbonate, an electrolyte having high electrical conductivity can be prepared, and therefore such a mixture can be used even more preferably.

[0070] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.

[0071] The electrolyte contains the above-mentioned fluoroethylene carbonate. The fluoroethylene carbonate may be present in the electrolyte or may be present in the form of a coating on the positive electrode surface or the negative electrode surface. The fluoroethylene carbonate may be included in an amount of 1 to 10 parts by weight based on 100 parts by weight of the electrolyte.

[0072] In addition to the constituent components of the electrolyte, the electrolyte may further include one or more additives such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.

[0073] A lithium secondary battery according to one embodiment of the present invention includes an assembly including a positive electrode, a negative electrode, a separator, and an electrolyte.

[0074] A further embodiment of the present invention provides a battery module including the above-mentioned lithium secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics and cycle characteristics, and therefore can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0075] The lithium secondary battery according to the embodiment of the present invention stably exhibits excellent discharge capacity, output characteristics, and cycle performance, and can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems, as well as portable devices such as mobile phones, notebook computers, and digital cameras. For example, the battery module or battery pack can be used as a power source for one or more medium- to large-sized devices, such as power tools, electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs), or power storage systems.

[0076] Below, preferred examples are presented to aid in understanding the present invention. However, these examples are merely illustrative of the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present description. It goes without saying that such changes and modifications fall within the scope of the appended claims.

[0077] Example 1 A negative electrode active material layer-forming composition including a negative electrode active material containing SiO and graphite (3 parts by weight of SiO based on 100 parts by weight of the negative electrode active material), a conductive material (carbon black, CNT), a binder (SBR), and a thickener (CMC) in a weight ratio of 95.6:1.0:2.3:1.1 was coated on a copper foil having a thickness of 10 μm so that the thickness in a dry state became 140 μm, and then dried to manufacture a negative electrode.

[0078] Li 1.0 Ni 0.86 Co 0.06 Mn 0.08 A positive electrode active material layer forming composition containing lithium nickel oxide O2, conductive material (CNT), and binder (PVDF) in a weight ratio of 97:1:2 was coated onto an aluminum foil having a thickness of 15 μm to a dry thickness of 130 μm, and then dried to prepare a positive electrode.

[0079] The positive electrode and the negative electrode were laminated with a separator interposed therebetween, and an electrolyte was injected to prepare a battery. The separator used was a 12 μm thick separator having a PE / PP / PE triple-layered base film with a coating layer containing Al2O3 and a PVDF binder, and the electrolyte used was 1M LiPF6, ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (volume ratio 3 / 7), and vinylene carbonate (VC) / propane sultone (PS) / fluoroethylene carbonate (FEC) (containing 3 parts by weight, 1.5 parts by weight, and 3 parts by weight, respectively, based on 100 parts by weight of electrolyte).

[0080] The values ​​of the above-mentioned formula 1 for the produced battery are shown in Table 1. The capacity retention rate when the produced battery was subjected to 200 cycles of charge and discharge at a specific temperature is shown in Table 2 below.

[0081] Comparative Example 1 The same procedure as in Example 1 was carried out, except that 10 parts by weight of SiO was contained per 100 parts by weight of the negative electrode active material.

[0082] Comparative Example 2 The same procedure as in Comparative Example 1 was carried out, except that fluoroethylene carbonate was not added to the electrolyte.

[0083] The efficiency constants of the electrode active materials used in the batteries manufactured in the Examples and Comparative Examples, the contents of the additive (fluoroethylene carbonate), and the values ​​of Equation 1 are shown in Table 1 below.

[0084] [Table 1]

[0085] The batteries manufactured in the examples and comparative examples were cycled at room temperature (25°C) by charging at 0.33C with constant current / constant voltage (CC / CV) up to 4.2V (0.05C cutoff) and discharging at 0.5C with constant current (CC) (2.5V cutoff). The number of cycles at which the batteries reached 80% of the initial capacity is shown in Table 2 below.

[0086] [Table 2]

[0087] As shown in Table 2, it was confirmed that the number of cycles required for the batteries of the Examples to reach 80% capacity was much greater than that required for the Comparative Examples.

Claims

1. A lithium secondary battery including a positive electrode, a separator, a negative electrode, and an electrolyte, The positive electrode includes a lithium composite transition metal compound including nickel (Ni) and cobalt (Co), The negative electrode includes a mixed negative electrode active material of a silicon-based active material and a carbon-based active material, the electrolyte comprises fluoroethylene carbonate; When the efficiency constants of the mixed negative electrode active material and the lithium composite transition metal compound are a and b, respectively, and the part by weight of the fluoroethylene carbonate is c based on 100 parts by weight of the electrolyte, a, b, and c satisfy the following formula 1: [Formula 1] [(b / a)×100-c]≦95 That is, a lithium secondary battery.

2. 2. The lithium secondary battery according to claim 1, wherein the lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) contains nickel in an amount of 80 mol % or more of metals other than lithium.

3. 2. The lithium secondary battery according to claim 1, wherein the lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) is a single particle.

4. The lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) is represented by the following Chemical Formula 1: [Chemical formula 1] Li a Ni (1-x-y) Co x M1 y M2 w O 2 In Chemical Formula 1, 1.0≦a≦1.5, 0≦x≦0.2, 0≦y≦0.2, 0≦w≦0.1, 0≦x+y≦0.2, M1 is at least one metal selected from the group consisting of Mn and Al; 2. The lithium secondary battery according to claim 1, wherein M2 is one or more metal elements selected from the group consisting of Ba, Ca, Zr, Ti, Mg, Ta, Nb, and Mo.

5. 2. The lithium secondary battery of claim 1, wherein the positive electrode comprises 90 to 100 parts by weight of the lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) based on 100 parts by weight of the positive electrode active material.

6. The silicon-based active material is SiO x (0≦x<2), SiM y 2. The lithium secondary battery of claim 1, comprising at least one of: (M is a metal; 1≦y≦4); and Si / C.

7. The lithium secondary battery according to claim 1 , wherein the silicon-based active material is present in an amount of 1 part by weight or more and less than 20 parts by weight based on 100 parts by weight of the mixed negative electrode active material.

8. 2. The lithium secondary battery of claim 1, wherein the fluoroethylene carbonate is contained in an amount of 1 to 10 parts by weight based on 100 parts by weight of the electrolyte.

Citation Information

Patent Citations

  • Positive electrode active material, positive electrode for secondary battery and nonaqueous electrolytic solution secondary battery using the same

    JP2003168434A

  • Method for manufacturing positive electrode active material for nonaqueous electrolyte secondary battery

    JP2017188444A

  • Method for manufacturing lithium ion secondary battery

    JP2018190582A

  • Positive electrode active material for lithium secondary battery and method for producing same

    JP2020520539A

  • Nonaqueous electrolyte secondary battery

    JP2022063677A